Towards ultra-responsive biodegradable polysaccharide humidity sensors. (December 2017) - Liakos, Ioannis L.; Mondini, Alessio; Filippeschi, Carlo; Mattoli, Virgilio; Tramacere, Francesca; Mazzolai, Barbara
Abstract: Sodium alginate is a biodegradable natural polymer that is derived from algae and is water soluble. Upon immersion in a CaCl2 solution, a sodium alginate water solution is cross-linked to form water-insoluble calcium alginate. When the sodium alginate water solution is immersed in the CaCl2 bath via a syringe pump, calcium alginate fibers are produced. By changing the CaCl2 concentration, calcium alginate fibers with different degrees of cross-linking can be produced. Such fibers were found to differ in mechanical and morphological properties, and more interestingly, were found to possess humidity sensing and conductive properties. Interestingly, the higher the CaCl2 concentration, the lower the degree of cross-linking, which produced softer fibers with better humidity sensing and conductive properties. The fibers were able to trap water in their structures, and a higher water content increased the conductivity due to the presence of an electrolyte salt in the fiber and due to the polyelectrolyte nature of the fiber itself. The cross-linking and percent shrinking degree, morphology and mechanical properties of the fibers were found to create significant changes in the conductivity and humidity sensing properties of the fibers. High humidity environments led to an increase in the conductivity of the fibers, whereas dry environments led to a decrease in the conductivity. The fibers, especially those with the highest CaCl2 concentration, were determined to be ultra-responsive to humidity changes and exhibited very good repetition in humidity cycles. These tailored fibers are proposed as novel biodegradable conductive materials for various humidity sensing, robotic and bio-robotic applications. Graphical abstract: Highlights: Calcium alginate fibers can be tailored to provide ultra-responsive humidity sensing properties. Water is absorbed and desorbed from the alginate fibers while conductivity is affected due to electrolyte and polyelectrolyte effect. Cross-linking degree of alginate fibers using CaCl2 greatly affects their humidity sensing and conductive properties. Such calcium alginate fibers can be used for biodegradable electronics and sensing devices.